Wear and microstructural properties of coatings on Weldox 700 steel - Özorak, Cihan; Okay, Faik; Özorak, Ebru; Islak, Serkan (Walter de Gruyter GmbH, 2020)
Abstract In this study, the wear and microstructure properties of some coatings produced on Weldox 700 steel were investigated via a high-velocity oxygen fuel (HVOF) technique. For the coating types, NiCrBSi, WCCo and CoNiCrAlY-based coatings were selected. Microstructure and phase formation were examined via scanning electron microscopy (SEM), X-ray diffraction and X-ray energy dispersive spectrometry. Wear tests of the substrate and coatings were made using the ball-on-disc method. It can be seen from the SEM images that the coating layers are metallurgically/ mechanically connected to the substrate and have a mostly homogeneous structure. The hardness measurement was taken from the top of the coatings. The hardness values of the coatings were significantly higher than those of the substrate. The coated substrates exhibit a very good tribological performance compared with the substrate. Depending on the load, the wear rate and coefficient of friction of the coatings were much lower as compared with the Weldox 700 steel substrate.
Keywords: 7. Clean energy; 6. Clean water